Prevalence and Impact of Coagulation Dysfunction in COVID-19 in China: A Meta-Analysis - Jin, Shanen; Jin, Yiyang; Xu, Bai; Hong, Jun; Yang, Xianghong (Thrombosis and Haemostasis, 2020)
Background The aim of this meta-analysis is to assess the prevalence of coagulation dysfunction in Chinese COVID-19 patients and to determine the association of coagulopathy with the severity and prognosis of COVID-19.Methods A meta-analysis of the prevalence of different abnormal coagulation indicators in COVID-19 patients in China was performed. The difference of coagulation indicators and the incidence of DIC were compared between severe cases and nonsevere cases as well as nonsurvivors and survivors, respectively.Results A total of 22 Chinese studies involving 4,889 confirmed COVID-19 inpatients were included. The average D-dimer value of COVID-19 patients is 0.67 µg/mL (95% confidence interval [CI]: 0.56–0.78), and 29.3% (95% CI: 20.1–38.5%) of patients showed elevated D-dimer values. Severe patients had significantly higher D-dimer levels and prolonged prothrombin time (PT) compared with nonsevere patients. Nonsurvivors had significantly higher D-dimer levels, prolonged PT, and decreased platelet count compared with survivors. In total, 6.2% (95% CI: 2.6–9.9%) COVID-19 patients were complicated by disseminated intravascular coagulation (DIC), in which the log risk ratio in nonsurvivors was 3.267 (95% CI: 2.191–4.342, Z = 5.95, p < 0.05) compared with that in survivors.Conclusion The prevalence of coagulopathy in Chinese COVID-19 inpatients is high, and both the abnormal coagulation indicators and DIC are closely associated with the severity and poor prognosis of these COVID-19 patients. Therefore, attention should be paid to coagulation dysfunction in COVID-19 patients. Closely monitoring of coagulation indicators and application of appropriate anticoagulation may improve the prognosis of COVID-19 inpatients in China.
Keywords: COVID-19; coagulopathy; disseminated intravascular coagulation; venous thromboembolism; anticoagulation